IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL TERHADAP KUALITAS LAPORAN KEUANGAN DI KABUPATEN GORONTALO - Fauziah Husain; Hardianti Mukrima (Jurnal Riset Akuntansi, 2025)
The purpose of this study is to evaluate how the implementation of Government Regulation No. 71 of 2010 regarding accrual-based Government Accounting Standards (SAP) in Gorontalo Regency impacts the quality of financial reports presented. This research employs a library research method, gathering data from various sources such as journals, books, and official government documents. It is hoped that this study will provide information to the public and the Regional Device Organization (SKPD) about how SAP influences the quality of financial reports. The findings indicate that although accrual-based SAP improves the quality of financial reports, there are several issues encountered during its application in Gorontalo Regency. Consequently, plans and strategies are needed to address these existing problems.